Approaches to Digital Profiling in the Financial Market - Ilina Tatyana; Piatina Elena (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2020)
Creating a “digital profile” is one of the points of the Russian national program Digital Economy [1]. A single biometric profile creation system is becoming the infrastructure basis for the digital transformation of the entire economy [2]. The process of forming a digital society is associated with the total digitization of all forms and types of relationships. At the same time, it is necessary to take into account the features, threats and trends of this process. The purpose of this article was to study the essential features and application of digital profiling of the financial market, defining the applications of this method and methodological approaches by examining existing expertise in other areas, and industries. The article summarizes information about the use of digital profiling in various industries. Areas of the financial market for the application of profiling were identified. The general characteristics are formulated and the features of the development of a methodological approach to profiling in the financial market are revealed. The criteria and principles of forming a digital profile of a market participant, relationships and patterns for improving the models of identification of participants and the market profile as a whole are presented.